(untitled) - Butterfield, H. (London, 1957)
This book intduce the historical importance of a theory of impetus, the conservatism of copernicus, the study of the heart down to William Harvey...
Keywords: Science,Science,Khoa học,Khoa học; History,Philosophy,Lịch sử,Triết học